Instructional functions of code-switching in the EFL classroom - YILMAZ VİRLAN, AYŞE (My University, 2023)
This study aims to identify how code-switching functions as an instructional method and discusses teachers’ perceptions of language choice and code-switching practices at the English Prep Program of a state university in Istanbul. Teachers’ language choice relates directly to pedagogical focus; therefore, the present study mainly intends to examine why instructors feel the need for code-switching while teaching. In this regard, the study also examines if there is a specific corpus that teachers follow while they are code-switching, by applying a mixed- method of data collection and analysis. Not only the teachers (N=6) but also students (N=63) were included in the study to investigate the issue from a broader perspective. The study unearthed that even though English is the primary instructional language in the classroom, coding from the second language to the first language is taking place in preparatory classes. The data analysis also indicated that all the instructors consciously or unconsciously as they reported- code-switched throughout their lessons to make up for the students\" language deficiency and to explain the concept that had no equivalent in the English language. The findings are important as they can help teachers to reflect on the instructional functions of their code-changing practices during instructions.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Social Sciences and Humanities; Education; Educational Sciences; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Code-switching; EFL teaching; Instructional Functions of Codeswitching; Language instruction; Second language learning